Biological Effects of Antifreeze Agents in Dental Formulations: Review Article (Journal of Pharma Insights and Research, 2025)
Antifreeze agents in dental formulations, particularly polyols like glycerin (10-40%), propylene glycol (5-20%), and sorbitol (10-30%), exhibit multifaceted biological interactions within the oral environment. Their molecular mechanisms operate through three primary pathways: osmotic regulation via aquaporin channels, protein stabilization through preferential exclusion, and membrane protection via hydroxyl group interactions. These agents have prominent effects on enamel remineralization by modulating calcium and phosphate ion dynamics, with glycerin showing a 15-20% enhancement in mineral uptake. Propylene glycol particularly influences dentinal fluid movement, reducing sensitivity by 30-40% through occlusion of dentinal tubules. The agents affect biofilm formation by altering surface energy properties, resulting in a 25-35% reduction in initial bacterial adhesion. Clinical studies have revealed their role in enhancing fluoride bioavailability by 40-50% through improved surface wetting characteristics. Concentration-dependent effects show optimal biological responses at 15-25% for glycerin and 8-15% for propylene glycol. Advanced microscopic and spectroscopic analyses have revealed these agents' influence on enamel crystal formation, showing a 10-15% increase in hydroxyapatite crystallinity. Their impact on salivary protein structures maintains oral homeostasis by preserving enzymatic activity at 85-90% efficiency. Recent literature has shown their role in stabilizing therapeutic ingredients, extending their retention time by 2-3 hours. The agents also demonstrate protective effects against thermal stress, maintaining protein stability up to 45°C, and contribute to pH buffering capacity within the range of 6.5-7.2